NDR1 protein kinase promotes IL‐17‐ and TNF‐α‐mediated inflammation by competitively binding TRAF3. (20th February 2017) - Ma, Chunmei; Lin, Wenlong; Liu, Zhiyong; Tang, Wei; Gautam, Rahul; Li, Hui; Qian, Youcun; Huang, He; Wang, Xiaojian
Abstract: Interleukin 17 (IL‐17) is an important inducer of tissue inflammation and is involved in numerous autoimmune diseases. However, how its signal transduction is regulated is not well understood. Here, we report that nuclear Dbf2‐related kinase 1 (NDR1) functions as a positive regulator of IL‐17 signal transduction and IL‐17‐induced inflammation. NDR1 deficiency or knockdown inhibits the IL‐17‐induced phosphorylation of p38, ERK1/2, and p65 and the expression of chemokines and cytokines, whereas the overexpression of NDR1 promotes IL‐17‐induced signaling independent of its kinase activity. Mechanistically, NDR1 interacts with TRAF3 and prevents its binding to IL‐17R, which promotes the formation of an IL‐17R‐Act1‐TRAF6 complex and downstream signaling. Consistent with this, IL‐17‐induced inflammation is significantly reduced in NDR1‐ deficient mice, and NDR1 deficiency significantly protects mice from MOG‐induced experimental autoimmune encephalomyelitis (EAE) and 2, 4, 6‐trinitrobenzenesulfonic acid (TNBS)‐induced colitis likely by its inhibition of IL‐17‐mediated signaling pathway. NDR1 expression is increased in the colons of ulcerative colitis (UC) patients. Taken together, these findings suggest that NDR1 is involved in the development of autoimmune diseases. Synopsis: IL‐17 induces tissue inflammation and is involved in many autoimmune reactions. This study shows that the nuclear kinase NDR1 interacts with TRAF3 and promotes the formation of IL‐17R‐Act1‐TRAF6 complexes, which trigger downstream signal transduction and inflammation. The nuclear Dbf2‐related kinase 1 (NDR1) promotes IL‐17‐induced inflammation in vitro and in vivo . NDR1 enhances IL‐17‐dependent signaling and inflammation by targeting TRAF3. NDR1 deficiency protects mice from experimental autoimmune encephalomyelitis (EAE) and TNBS‐induced colitis. NDR1 expression is increased in the colon of ulcerative colitis (UC) patients. Abstract : IL‐17 induces tissue inflammation and is involved in many autoimmune reactions. This study shows that the nuclear kinase NDR1 interacts with TRAF3 and promotes the formation of IL‐17R‐Act1‐TRAF6 complexes, which trigger downstream signal transduction and inflammation.